Empowering a local economy in Indonesia through tourism and good practice - Fitrianto, Achmad Room; Halim, Abdul; Mcmichael, Heath (Humanities, Arts and Social Sciences Studies, 2024)
This article explores how a group of stakeholders worked collaboratively on an economic initiative to develop an abandoned limestone mine site in Sekapuk village, Gresik, Indonesia. A sustainable livelihood framework using qualitative methods is used in the analysis. The fieldwork reveals that in Sekapuk, village-owned companies and village officials cooperated to maximise the utility of their assets and economic advantage by designing and implementing two community programs. The first program, known as the TAPLUS (Tabungan Plus) Savings and Investment Plan, used community funds for converting an abandoned limestone mine site into a viable tourist destination. The second program sought to empower women economically by enabling single mothers to access low-interest, soft loans. The program provided these women and other women’s groups with the means by which they could become involved in tourism activities at village level. Through implementation of these initiatives, the Sekapuk community benefitted in a variety of ways; by repurposing an abandoned mine as a domestic tourist destination for economic gain and by empowering residents of the village.